تقنيات التواصل الفعال لمقدمي البرامج في الإذاعات الإلكترونية وأثرها على الطلبة الجامعيين - عكيشي,ادم; بوديار,سلمى (University of Eloued جامعة الوادي, 2024)
هدفت هذه الدراسةإلى معرفةالعوامل التي تؤثرفي نجاح مقدمي البرامج في الإذاعات ا لالكترونيةفيمايتعلق بجذب جمهورطلبةالإعلاموالاتصال بجامعةالوادي،حيث اعتمدت هذه الدراسةعلى المنهج الوصفي التحليلي،كماتم تصميم استمارةاستبانةوتوزيعهاعلى عينةمسحيةمن طلبةعلوم الإعلام والاتصال بجامعةالوادي،إذ تمت المعاينةبطريقةغيراحتامالية قصدية،وتكون مجتمع الدراسةمن جميع طلبةوطالبات قسم الاعلام والاتصال بجامعةالشهيدحمه لخضربالوادي،حيث كانت عينةالدراسة (100) مفردة. وقدتوصلت الدراسةإلى النتائج التالية: أن طلبةقسم الاعلام والاتصال بجامعةالشهيدحمة لخضريتعرضون لإذاعةالجديدبشكل شبهي وميوذلكراجع للفئةالعمريةللطلبةالذين يتراوح معظمهم مابين 22 الى 25 سنة. -إن طلبةقسم الاعلام والاتصال بجامعةالشهيدحمةلخضريفضلون متابعةالبث الحيل برامج إذاعةالجديد. -خلصت الدراسةأنغالبيةالطلبةتجذبهم سلاسةوسلامةاللغةالاعلاميةالموظفةمن قبل مقدمي البرامج بإذاعةالجديدوتدفعهم للتعرض لبرامجها. - يستندأغلب مقدمي البرامج بإذاعةالجديدالإلكترونيةإلى الأمثلةالواقعيةلتوضيح الأحداث المهمةعبربرامجهم الإذاعية. This study aimed to find out the factors that affect the success of program presenters on electronic radio with regard to attracting an audience of media and communication students at the University of the Valley. This study relied on the descriptive and analytical approach. A questionnaire form was also designed and distributed to a survey sample of students of media and communication sciences at the University of the Valley. The sampling was carried out in a non-probabilistic, intentional way, and the study population consisted of all male and female students of the Department of Media and Communication at the University of Shahid Hama Lakhdar in El Oued, where the sample was Study (100) words . The study reached the following results: - Students of the Department of Media and Communication at Shahid Hama Lakhdar University are exposed to... Al-Jadeed Radio is broadcast almost daily, due to the age group of the students, most of whom range between... - Students of the Department of Media and Communication at the University of Chahid Hamma Lakhdar prefer to follow the live broadcast of Radio Al-Jadeed programs. -The majority of students are attracted by the smoothness and integrity of the media language used by the program presenters on Al-Jadeed Radio and encourage them to be exposed to its programs. -Most of the presenters on Al-Jadeed Electronic Radio rely on real-life examples to illustrate important events in their radio programs. - The methods used by Al-Jadeed Radio program presenters help the sample acquire activation and presentation skills. -The study showed that program presenters on Al-Jadeed Radio play a major role in encouraging viewers to participate and interact. - Clothes and fashion influence most of the sample's members in their understanding of the media message. -Most of the study sample members believe that body language and facial expressions are important The programs on Al-Jadeed Radio are consistent with the content of the message presented.
Keywords: مقدمي البرامج; الإذاعات الإلكتروينة; التأثيرـتقنيات التواصل الفعال